Observing waterflow within an embankment dam using self-potential monitoring - Bernd Kulessa (Dams and Reservoirs, 2023)
Geophysics has become a fundamental tool for the characterisation of dam structures and the identification of subsurface defects. However, evolving a geophysical technique to a monitoring solution for observing subsurface water flow is considered an important step to help water companies and governing bodies achieve their aims related to climate resilience, water supply targets and for lengthening the design life of critical infrastructure. The paper shows how monitoring of self-potential voltages using the SPiVolt system developed by TerraDat has successfully mapped water flow through the downstream shoulder of a Victorian-era embankment dam, and how these water flow paths responded to changes in the reservoir level and weather events such as heatwaves and rainfall. The study has also shown the importance of using a multi-technique geophysical survey to provide a wider context and deeper understanding of dam structures. The methodology described in this paper has the potential to not only provide a low-cost solution to monitoring embankment dams but can also be applied to numerous scenarios including landslide investigations, peatlands and flood defences.